(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
At the present stage of societal development, in the context of updating the content and methods of education, it is becoming clear that significant changes are needed in the university training of teachers, including defectologists. This is based on developing a new pedagogical paradigm founded on principles of humanism and democracy, and recognizing children’s right to education in accordance with modern requirements and individual characteristics.